The economy-wide impact of Sudan’s ongoing conflict: Implications on economic activity, agrifood system and poverty - Siddig, Khalid; Raouf, Mariam; Ahmed, Mosab O. M. (International Food Policy Research Institute, 2023)
The armed conflict between the Sudanese Armed Forces (SAF) and Rapid Support Forces (RSF) in Sudan entered its sixth month since it erupted on April 15th, 2023, with no signs of ending soon. The war has caused severe humanitarian catastrophe, destroyed key infrastructure, and constrained trade and production activities. Moreover, it disrupted access to public utilities, financial services, and markets, hence, triggering considerable scarcity of goods and services. In this paper, we utilize a Social Accounting Matrix (SAM) Multiplier modeling framework to assess the economywide implications of these disruptions of economic activity, productive resources, and livelihoods. Results reveal that the economy would shrink to nearly half its size before the war, household incomes decline by more than 40 percent in urban and rural areas, and the number of poor people increase by 1.8 million if the war continues until the end of the year. The impact would have been two thirds less should the war have ended before July 2023 and would be one third less if it would end before October 2023. This study therefore calls for rapid interventions from all relevant parties to help reach an end to the fighting.